2022
DOI: 10.3389/fphar.2022.949644
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the potential mechanism and molecular targets of Fufang Xueshuantong capsule for the treatment of ischemic stroke based on network pharmacology and molecular docking

Abstract: Fufang Xueshuantong (FFXST) capsule is a traditional Chinese medicine (TCM) preparation used to activate blood circulation, resolve stasis, benefit qi, and nourish yin in clinical practice. However, its potential mechanism and molecular targets after ischemic stroke (IS) have not been investigated. The aim of this research was to investigate the molecular mechanisms of FFXST in the treatment of IS based on network pharmacology and molecular docking. We used the Traditional Chinese Medicine Systems Pharmacology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…It is reported that salvianolic acids promoted angiogenesis and neurological recovery by regulating STAT3 signaling pathway after ischemia (Li et al, 2017). In addition, Wang et al proved that the core target of ischemic stroke in Fufang Xueshuantong treatment was STAT1, STAT3 through the method of network pharmacology, which was consistent with our predicted results (Wang et al, 2022). Therefore, these core genes inhibit inflammation and apoptosis, protect vascular endothelial injury in order to inhibit thrombosis in ischemic stroke rats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is reported that salvianolic acids promoted angiogenesis and neurological recovery by regulating STAT3 signaling pathway after ischemia (Li et al, 2017). In addition, Wang et al proved that the core target of ischemic stroke in Fufang Xueshuantong treatment was STAT1, STAT3 through the method of network pharmacology, which was consistent with our predicted results (Wang et al, 2022). Therefore, these core genes inhibit inflammation and apoptosis, protect vascular endothelial injury in order to inhibit thrombosis in ischemic stroke rats.…”
Section: Discussionsupporting
confidence: 86%
“…Network pharmacology seeks targets of drugs and diseases from public databases to analyze the mechanism of drug action from the perspective of biological balance, which helps to elucidate the interactions among compounds, genes, and diseases (Li et al, 2020;Wang et al, 2021a;Wang et al, 2022). In this paper, we first used the method of network pharmacology to predict the effect of phenolic acids in the prevention of ischemic stroke, and then screened the antiplatelet effect through in vitro antiplatelet experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the pathogenesis of ischemic stroke, the limitations of therapeutic drugs and the very large international and domestic needs, an increasing number of researchers are studying traditional Chinese medicines as important ways to treat ischemic stroke [9][10][11]. Notoginseng leaf triterpenes (PNGL), a total saponin extract of Panax notoginseng stems and leaves, attenuates neuronal apoptosis [12] and ameliorates mitochondrial oxidative injury caused by ischemia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Bunge, and Scrophularia ningpoensis Hemsl . It has the function of promoting blood circulation, removing blood stasis, tonifying qi, and nourishing yin and could be used clinically for the treatment of stable angina pectoris and cerebrovascular diseases ( Peng et al, 2022 ; Wang et al, 2022 ). Peng et al (2022) observed the intervention effect of FXST on DCM by establishing a STZ-induced diabetic rat model.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%
“…Clinically, DCM can be divided into two stages according to its typical features. The early stage is characterized by diastolic damage and left ventricular hypertrophy without vascular defects, and the late stage is mainly characterized by systolic dysfunction and myocardial fibrosis ( Wang et al, 2022 ; Zhou et al, 2023 ). Although the pathogenesis of DCM is complex, after long-term exploration, scholars generally believe that the occurrence and development of DCM is mainly related to glucose and lipid metabolism disorders, microvascular endothelial dysfunction, apoptosis, advanced glycation end product (AGE) deposition, myocardial inflammation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%